VOCATIONAL CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF GRADUATES (CASE STUDY AT AL HUDA VOCATIONAL SCHOOL KEDUNGWUNGU ANJATAN DISTRICT, INDRAMAYU DISTRICT) - Sutrisno (Media Inovasi Pendidikan dan Publikasi, 2024)
This research was motivated by the speech of the Governor of West Java, Ridwan Kamil, which was published on jabartribunnews.com in 2021, conveying about the implementation of training based on industrial cooperation and the world of work related to vocational and vocational training. Ridwan Kamil said that the regional government of West Java Province was encouraging industry to enter college and provide applied knowledge, especially to Vocational High Schools (SMK). This step was taken to ensure that vocational school graduates are ready to work because vocational school graduates are the biggest cause of unemployment in West Java. This problem arises, one of the causes is the quality of graduates who lack competence in accordance with the demands of the world of work. For educational services, quality is a big issue, especially in relation to the quality of graduates, and has recently received special attention, becoming a hot topic of discussion among education observers, government circles, commercial and educational institutions and others. The low quality of teaching staff, the high cost of education and poor curriculum management are some of the causes of the low quality of graduates. The focus of research in this thesis is (1) How does the vocational curriculum plan improve the quality of graduates at Al Huda Vocational School, Kedungwungu?, (2) How does the vocational curriculum plan implement in improving the quality of graduates at Al Huda Vocational School, Kedungwungu?, and (3) How does the curriculum be evaluated? vocational education in improving the quality of graduates at Al Huda Vocational School, Kedungwungu? This research aims to (1) Analyze vocational curriculum planning in improving the quality of graduates at Al Huda Vocational School, Kedungwungu, (2) Analyze the implementation of the vocational curriculum in improving the quality of graduates at Al Huda Vocational School, Kedungwungu, and (3) Analyzing vocational curriculum evaluations in improving the quality of graduates at Al Huda Kedungwungu Vocational School. A qualitative type with a case study approach was used in this research. The object of this research is Al Huda Kedungwungu Vocational School, Anjatan District, Indramayu Regency, West Java. The data collection procedure uses in-depth interviews, non-participatory observation